« C'est la vie qui exagère » : quelques remarques à propos de la mort de Balzac dans « La 628- E8 » d'Octave Mirbeau - Vareille, Arnaud (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
In the novel La 628-E8 declaring his disgust with art, as if looking for a confirmation of his feeling, Octave Mirbeau dedicates three subchapters of his work to Balzac, in order to create a biography, taking into account only the figure of the writer as a man, leaving out his oeuvre. But while the text seems to be a farewell with literature and with its effect of artificiality, praising the virtues of the text-document containing elements which are exclusively the author's own, a fragment which describes Balzac's death makes the word emerge in all its complexity: the word as an evidence of reality or as an invention. Thus, through its nature of elusiveness, it becomes a reconciliation between literature and life.
"It is life that exaggerates": some remarks on Balzac's death in Octave Mirbeau's novel La 628-E8